Habitat provision is a major driver of native bird communities in restored urban forests. Issue 7 (25th April 2022) - Elliot Noe, Elizabeth; Innes, John; Barnes, Andrew D.; Joshi, Chaitanya; Clarkson, Bruce D.
Abstract: Urbanization, and the drastic loss of habitat it entails, poses a major threat to global avian biodiversity. Ecological restoration of urban forests is therefore increasingly vital for native bird conservation, but control of invasive predators may also be needed to sustain native bird populations in cities where species invasions have been particularly severe. We evaluated restoration success by investigating changes in native bird communities along a restoration chronosequence of 25 restored urban forests representing 72 years of forest development, which we compared to two target reference systems and a control system. We hypothesized that total species richness and relative abundance of native forest birds would increase with the age of restoration planting. We further hypothesized that relative abundance of rats, possums and cats would negatively impact native birds, while amount of native forest in the surrounding landscape would have a positive effect. We used structural equation modelling (SEM) to investigate the relative influence of forest structure (complexity index, tree height, canopy openness, basal area, species richness and density), landscape attributes (patch area, perimeter length, landscape composition within three buffer zones, distance to the nearest road and water source) and invasive mammalian predator indices of relative abundance on total species richness and relative abundance of native forest birds. Species richness increased with age of restoration planting, with community composition progressing towards that found in target reference systems. SEM revealed that years restored was a direct driver of bird species richness but an indirect driver of abundance, which was directly driven by canopy openness. Contrary to our predictions, invasive mammals had no significant effect on native bird species richness or abundance. Our results demonstrate that provision and improvement of habitat quantity and quality through restoration is the vital first step to re‐establishing native forest bird communities in cities. Abstract : We evaluated restoration success by investigating changes in native bird communities along a restoration chronosequence of 25 restored urban forests representing 72 years of forest development. Our results demonstrate that provision and improvement of habitat quality through restoration is the vital first step to re‐establishing native forest bird communities in cities.